Preparation method of humidity-responsive cellulose nanocrystal structural color film
By controlling the hydrolysis time of sulfuric acid, cellulose nanocrystals with different aspect ratios are prepared, and the phase separation problem of cellulose nanocrystal films is solved after the addition is introduced, the uniformity and color regulation of humidity-responsive films are achieved, and the recycling of waste cotton is promoted. Use responsive discoloration with humidity changes.
Patent Information
- Application Number
- CN202411322724.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The introduction of additives into cellulose nanocrystalline suspension will lead to phase separation, hindering the uniformity of cellulose nanocrystalline films and the self-assembly of chiral nematic phase structures, and affecting the uniformity of the film structure.
By controlling the time of sulfuric acid hydrolysis, waste cotton regenerated cellulose nanocrystals with different aspect ratios are prepared, and self-assembly is used to regulate self-assembly to form a uniform and humidity-responsive cellulose nanocrystal structure color film with different colors, avoiding phase caused by additives Separation problem.
The uniformity and color regulation of humidity-responsive cellulose nanocrystal film is achieved. The film has responsive discoloration characteristics to environmental humidity changes, and maintains good humidity response performance in multiple cycles, and promotes efficient recycling and utilization of waste cotton. .
Smart Images

Figure CN119286010A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of humidity responsive color-changing materials, and in particular relates to a method for preparing a humidity responsive cellulose nanocrystal structural color film. Background Art
[0002] Cellulose is the most widely known and most abundant carbohydrate in nature, accounting for about 50% of the total carbon content of the plant kingdom. It has the advantages of excellent mechanical properties, good biocompatibility, easy availability and low cost. Cellulose nanocrystals prepared by hydrolyzing cellulose with sulfuric acid usually have anisotropic rods and negative surface charges, so they can be well dispersed in water. After evaporation, the colloidal cellulose nanocrystal suspension spontaneously assembles into a solid film with a chiral nematic phase structure and structural color. At the same time, the cellulose nanocrystal film retains its left-handed structure during the evaporation process and can reflect left-handed circularly polarized light. Photonic crystals are spatially ordered structures whose lattice parameters are equivalent to the wavelength of the propagating light. Since the periodicity of the chiral nematic phase spiral structure of cellulose nanocrystals matches the wavelength of visible light, the cellulose nanocrystal film can also be regarded as a photonic crystal, so it can be used as a sensor for visual recognition.
[0003] At present, the color of cellulose nanocrystal film can be regulated by introducing additives. Additives are usually introduced into cellulose nanocrystal suspensions. The additives can be monomers such as acrylamide and acrylic acid, water-soluble polymers (such as polyvinyl alcohol) and polyethylene glycol and latex nanoparticles. The introduction of additives into cellulose nanocrystal suspensions can obtain adjustable pitch of cellulose nanocrystals, thereby controlling the photonic band gap. The additives combine with cellulose nanocrystals, participate in self-assembly and form a chiral nematic structure. The reflection wavelength of cellulose nanocrystal film prepared by the method of introducing additives can be adjusted within the visible spectrum, which provides the possibility of preparing sensitive sensors for visual recognition. However, the addition of these additives will cause phase separation, affect the self-assembly of the chiral nematic phase structure of the film, and cause large cracks in the pitch, which affects the uniformity of the film structural color. Summary of the invention
[0004] [Technical issues]
[0005] The present invention aims to solve the problem that the introduction of additives into the cellulose nanocrystal suspension will cause phase separation and hinder the uniformity of the cellulose nanocrystal film.
[0006] [Technical solution]
[0007] In order to solve the above problems, the present invention provides a method for preparing a humidity-responsive cellulose nanocrystal structural color film, by controlling the time of sulfuric acid hydrolysis to prepare waste cotton regenerated cellulose nanocrystals with different aspect ratios, and utilizing the nanocrystals to regulate self-assembly to obtain a uniform humidity-responsive structural color film with different colors, thereby solving the problem of phase separation caused by conventional polymer-regulated film color and difficulty in forming a uniform chiral nematic phase structure.
[0008] The present invention provides a method for preparing a humidity-responsive cellulose nanocrystal structural color film, which specifically comprises the following steps:
[0009] (1) The alkali-pretreated waste cotton powder was hydrolyzed with sulfuric acid to prepare a cellulose nanocrystal suspension, and regenerated cellulose nanocrystal suspensions CNC with different aspect ratios were prepared by controlling the time of sulfuric acid hydrolysis. n ;
[0010] (2) CNC suspensions of regenerated cellulose nanocrystals with different aspect ratios n The mixture is uniformly mixed in different proportions and evaporated to induce self-assembly to form a film, thereby obtaining a humidity-responsive cellulose nanocrystal structural color film.
[0011] In one embodiment of the present invention, in step (1), the waste cotton powder is subjected to alkali pretreatment by soaking the waste cotton powder in a NaOH solution with a mass concentration of 3 to 10% for 8 to 10 hours.
[0012] In one embodiment of the present invention, in step (1), a regenerated cellulose nanocrystal suspension CNC having different aspect ratios is n The mass concentration is 2.0~8.4%.
[0013] In one embodiment of the present invention, in step (1), the mass concentration of sulfuric acid is 60-65%.
[0014] In one embodiment of the present invention, in step (1), a regenerated cellulose nanocrystal suspension CNC having different aspect ratios is n In the experiment, the aspect ratio of regenerated cellulose nanocrystals is 15-35.
[0015] In one embodiment of the present invention, in step (2), the regenerated cellulose nanocrystal suspension CNC having different aspect ratios n , n represents the acid hydrolysis time, and the hydrolysis time is 30 to 90 minutes.
[0016] In one embodiment of the present invention, in step (2), when n is 60min and 30min, the obtained CNC 60 and CNC 30The mixture was mixed evenly in a mass ratio of 1:9 and evaporated to induce self-assembly film; when n was 70min and 40min, the obtained CNC 70 and CNC 40 The mixture was mixed evenly in a mass ratio of 2:8 and evaporated to induce self-assembly film; when n was 80min and 50min, the obtained CNC 80 and CNC 50 The mixture was mixed evenly in a mass ratio of 4:6 and evaporated to induce self-assembly film; when n was 90min and 60min, the obtained CNC 90 and CNC 60 The mixture was mixed uniformly at a mass ratio of 9:1 and evaporated to induce self-assembly film; when n was 90min and 30min, the obtained CNC 90 and CNC 30 The mixture was mixed evenly at a mass ratio of 8:2 and evaporated to induce self-assembly film.
[0017] In one embodiment of the present invention, in step (2), the time for evaporation-induced self-assembly is 4 to 6 days.
[0018] The invention provides a humidity-responsive cellulose nanocrystal structural color film prepared by the method described above.
[0019] The present invention also provides applications of the humidity-responsive cellulose nanocrystal structural color film in the fields of environmental detection, medical diagnostic tools, and food processing safety.
[0020] [Beneficial Effects]
[0021] (1) Cellulose nanocrystals were regenerated from waste cotton by acid hydrolysis, and humidity-responsive chiral nematic structural color films were prepared by evaporation-induced self-assembly. Regenerated cellulose nanocrystals with different aspect ratios were prepared by controlling the time of sulfuric acid hydrolysis. Cellulose nanocrystals with different aspect ratios were then self-assembled together to obtain humidity-responsive films with different colors (blue, cyan, yellow, and orange).
[0022] (2) When the relative humidity increases from 11% to 97%, the color of the film changes from blue to yellow and then to red, and the diffraction peak moves from 494nm to 621nm and then to 723nm. The film of the present invention has the characteristic of responding to the change of humidity in the environment and changing color. There is no obvious loss of humidity responsive color changing performance within 10 cycles, and the repeatability of its humidity responsive performance is good.
[0023] (3) Cellulose nanocrystals with different aspect ratios are polymers with excellent compatibility and affinity. They can not only adjust the structural color of the cellulose nanocrystal film, but also do not affect the uniformity of the film, thus solving the problem that the introduction of additives into the cellulose nanocrystal suspension will cause phase separation and hinder the uniformity of the cellulose nanocrystal film.
[0024] (4) The present invention realizes the efficient recycling of waste cotton, which is beneficial to the reuse of waste resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The color change of the regenerated nanocrystalline humidity-responsive color-changing structural color film of Example 5 at different relative humidities is shown in the figure (a); the UV-Vis spectrum (b); and the cyclic response diagram (c);
[0026] Figure 2 This is the SEM image of the cross-section of the regenerated nanocrystal humidity-responsive color-changing structural color film in Example 5. DETAILED DESCRIPTION
[0027] CNC film real-life image shooting: Place the CNCs film on a black background paper and use a camera to take a picture from directly above the sample.
[0028] UV-Vis spectroscopy (UV-Vis) test method for CNC film: Prepare different relative humidity using saturated salt solution, place CNC film in bottles containing different relative humidity, and let stand for 5 minutes. Adjust the UV-Vis spectrometer (LAMBDA950) to reflection mode, perform calibration, baseline correction, etc. Then place the CNC film in the UV-Vis spectrometer for testing to obtain the UV-Vis reflectance spectrum.
[0029] Particle size analysis test method: Prepare a CNC suspension with a mass fraction of 1% and place it in a cuvette, and test it in a particle size analyzer.
[0030] Scanning electron microscopy (SEM) test method of CNC film: Scanning electron microscopy characterization was performed on a 5kV cold field emission scanning electron microscope (Hitachi SU8100). The CNC film sample was brittle fractured with liquid nitrogen, and the cross section was pasted upward on the carbon conductive glue on the scanning stage, and then it was made conductive by gold sputter coating before analysis, and the morphology of the CNC film was observed.
[0031] Example 1
[0032] A method for preparing a regenerated nanocrystalline humidity-responsive color-changing structural color film, the specific steps are as follows:
[0033] (1) Soaking the crushed waste cotton powder in a NaOH solution with a mass concentration of 3% for 10 hours, and washing with distilled water to obtain the waste cotton powder after alkali pretreatment;
[0034] (2) Adding the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 65%, heating and stirring for hydrolysis for 60 minutes, controlling the temperature at 45°C and the stirring speed at 200 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, adding distilled water for dilution, and then centrifugation washing at a speed of 6000 r / min for 8 minutes to remove the residual acid until it is neutral, to obtain a cellulose nanocrystal suspension CNC 60 ; Cellulose nanocrystal suspension CNC 60 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:100, and ultrasonic treatment was performed with an ultrasonic power of 500 W and an ultrasonic time of 20 min. The cellulose nanocrystal suspension CNC with a mass concentration of 2.5% was obtained. 60 ;Cellulose nanocrystals CNC 60 The length is 163.2±24nm, the diameter is 6.0±0.2nm, and the aspect ratio is 27;
[0035] (3) Adding the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 65%, heating and stirring for hydrolysis for 30 minutes, controlling the temperature at 45°C and the stirring speed at 200 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, adding distilled water for dilution, and then centrifugation washing at a speed of 6000 r / min for 8 minutes to remove the residual acid until it is neutral, to obtain a cellulose nanocrystal suspension CNC 30 ; Cellulose nanocrystal suspension CNC 30 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:100, and ultrasonic treatment was performed with an ultrasonic power of 500 W and an ultrasonic time of 20 min. The cellulose nanocrystal suspension CNC with a mass concentration of 2.5% was obtained. 30 ;Cellulose nanocrystals CNC 30 The length is 223.6±18nm, the diameter is 7.5±0.4nm, and the aspect ratio is 30;
[0036] (4) The cellulose nanocrystal suspension CNC with a mass concentration of 2.5% was prepared by evaporation film forming method. 60 and CNC 30 The mixture was evenly mixed at a mass ratio of 1:9, and then the mixed solution was transferred to a polystyrene watch glass, evaporated to dryness at room temperature and evaporated for 6 days to self-assemble into a film, thereby obtaining a blue humidity-responsive cellulose nanocrystal structural color film.
[0037] Example 2
[0038] A method for preparing a regenerated nanocrystalline humidity-responsive color-changing structural color film, the specific steps are as follows:
[0039] (1) Soaking the crushed waste cotton powder in a NaOH solution with a mass concentration of 3% for 9 hours, and washing with distilled water to obtain the waste cotton powder after alkali pretreatment;
[0040] (2) Add the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 62%, heat and stir to hydrolyze for 70 minutes, and control the temperature at 50°C and the stirring speed at 250 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, add distilled water to dilute, and then centrifuge and wash at a speed of 5500 r / min for 9 minutes to remove the residual acid until it is neutral, and obtain a cellulose nanocrystal suspension CNC 70 ; Cellulose nanocrystal suspension CNC 70 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:150, and ultrasonic treatment was performed with an ultrasonic power of 500 W and an ultrasonic time of 15 min. The cellulose nanocrystal suspension CNC with a mass concentration of 4% was obtained. 70 ;Cellulose nanocrystals CNC 70 The length is 143.2±26nm, the diameter is 5.8±0.2nm, and the aspect ratio is 24;
[0041] (3) Add the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 62%, heat and stir to hydrolyze for 40 minutes, and control the temperature at 50°C and the stirring speed at 250 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, add distilled water to dilute, and then centrifuge and wash at a speed of 5500 r / min for 9 minutes to remove the residual acid until it is neutral, and obtain a cellulose nanocrystal suspension CNC 40 ; Cellulose nanocrystal suspension CNC 40 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:150, and ultrasonic treatment was performed with an ultrasonic power of 500 W and an ultrasonic time of 15 min. The cellulose nanocrystal suspension CNC with a mass concentration of 4% was obtained. 40 ;Cellulose nanocrystals CNC 40 The length is 188.2±23nm, the diameter is 6.5±0.5nm, and the aspect ratio is 29;
[0042] (4) Using the evaporation film forming method, a 4% cellulose nanocrystal suspension CNC 70 and CNC 40The mixture was evenly mixed in a mass ratio of 2:8, and then the mixed solution was transferred to a polystyrene watch glass, evaporated to dryness at room temperature and evaporated for 6 days to self-assemble into a film, thereby obtaining a blue-green humidity-responsive cellulose nanocrystal structural color film.
[0043] Example 3
[0044] A method for preparing a regenerated nanocrystalline humidity-responsive color-changing structural color film, the specific steps are as follows:
[0045] (1) Soaking the crushed waste cotton powder in a NaOH solution with a mass concentration of 3% for 8 hours, and washing with distilled water to obtain the waste cotton powder after alkali pretreatment;
[0046] (2) Add the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 61%, heat and stir to hydrolyze for 80 minutes, and control the temperature at 55°C and the stirring speed at 300 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, add distilled water to dilute, and then centrifuge and wash at a speed of 5000 r / min for 8 minutes to remove the residual acid until it is neutral, and obtain a cellulose nanocrystal suspension CNC 80 ; Cellulose nanocrystal suspension CNC 80 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:200, and ultrasonic treatment was performed with an ultrasonic power of 1000 W and an ultrasonic time of 15 min. The cellulose nanocrystal suspension CNC with a mass concentration of 6% was obtained. 80 ;Cellulose nanocrystals CNC 80 The length is 123.2±31nm, the diameter is 5.6±0.2nm, and the aspect ratio is 21;
[0047] (3) Add the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 61%, heat and stir to hydrolyze for 50 minutes, and control the temperature at 55°C and the stirring speed at 300 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, add distilled water to dilute, and then centrifuge and wash at a speed of 5000 r / min for 8 minutes to remove the residual acid until it is neutral, and obtain a cellulose nanocrystal suspension CNC 50 ; Cellulose nanocrystal suspension CNC 50 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:200, and ultrasonic treatment was performed with an ultrasonic power of 1000 W and an ultrasonic time of 15 min. The cellulose nanocrystal suspension CNC with a mass concentration of 6% was obtained. 50 ;Cellulose nanocrystals CNC 50 The length is 177.2±23nm, the diameter is 6.3±0.5nm, and the aspect ratio is 28;
[0048] (4) The cellulose nanocrystal suspension CNC with a mass concentration of 6% was prepared by evaporation film forming method. 80 and CNC 50 The mixture was evenly mixed in a mass ratio of 4:6, and then the mixed solution was transferred to a polystyrene watch glass, evaporated to dryness at room temperature and evaporated for 5 days to self-assemble into a film, thereby obtaining a yellow humidity-responsive cellulose nanocrystal structural color film.
[0049] Example 4
[0050] A method for preparing a regenerated nanocrystalline humidity-responsive color-changing structural color film, the specific steps are as follows:
[0051] (1) Soaking the crushed waste cotton powder in a NaOH solution with a mass concentration of 3% for 8 hours, and washing with distilled water to obtain the waste cotton powder after alkali pretreatment;
[0052] (2) Add the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 60%, heat and stir to hydrolyze for 90 minutes, and control the temperature at 60°C and the stirring speed at 300 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, add distilled water to dilute, and then centrifuge and wash at a speed of 4000 r / min for 10 minutes to remove the residual acid until it is neutral, and obtain a cellulose nanocrystal suspension CNC 90 ; Cellulose nanocrystal suspension CNC 90 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:150, and ultrasonic treatment was performed with an ultrasonic power of 1500 W and an ultrasonic time of 10 min. The cellulose nanocrystal suspension CNC with a mass concentration of 8.4% was obtained. 90 ;Cellulose nanocrystals CNC 90 The length is 100.1±20nm, the diameter is 5.5±0.3nm, and the aspect ratio is 18;
[0053] (3) Add the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 60%, heat and stir to hydrolyze for 50 minutes, and control the temperature at 60°C and the stirring speed at 300 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, add distilled water to dilute, and then centrifuge and wash at a speed of 4000 r / min for 10 minutes to remove the residual acid until it is neutral, and obtain a cellulose nanocrystal suspension CNC 60 ; Cellulose nanocrystal suspension CNC 60 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:150, and ultrasonic treatment was performed with an ultrasonic power of 1500 W and an ultrasonic time of 10 min. The cellulose nanocrystal suspension CNC with a mass concentration of 8.4% was obtained. 60 ;Cellulose nanocrystals CNC 60The length is 163.2±24nm, the diameter is 6.0±0.2nm, and the aspect ratio is 27;
[0054] (4) The cellulose nanocrystal suspension CNC with a mass concentration of 8.4% was prepared by evaporation film forming method. 90 and CNC 60 The mixture was evenly mixed in a mass ratio of 9:1, and then the mixed solution was transferred to a polystyrene watch glass, evaporated to dryness at room temperature and evaporated for 4 days to self-assemble into a film, thereby obtaining an orange humidity-responsive cellulose nanocrystal structural color film.
[0055] Example 5
[0056] A method for preparing a regenerated nanocrystalline humidity-responsive color-changing structural color film, the specific steps are as follows:
[0057] (1) Soaking the crushed waste cotton powder in a NaOH solution with a mass concentration of 3% for 8 hours, and washing with distilled water to obtain the waste cotton powder after alkali pretreatment;
[0058] (2) Add the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 64%, heat and stir to hydrolyze for 90 minutes, and control the temperature at 45°C and the stirring speed at 300 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, add distilled water to dilute, and then centrifuge and wash at a speed of 5000 r / min for 10 minutes to remove the residual acid until it is neutral, and obtain a cellulose nanocrystal suspension CNC 90 ; Cellulose nanocrystal suspension CNC 90 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:200, and ultrasonic treatment was performed with an ultrasonic power of 1500 W and an ultrasonic time of 10 min. The cellulose nanocrystal suspension CNC with a mass concentration of 4.2% was obtained. 90 ;Cellulose nanocrystals CNC 90 The length is 100.1±20nm, the diameter is 5.5±0.3nm, and the aspect ratio is 18;
[0059] (3) Add the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 64%, heat and stir to hydrolyze for 30 minutes, and control the temperature at 45°C and the stirring speed at 300 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, add distilled water to dilute, and then centrifuge and wash at a speed of 5000 r / min for 10 minutes to remove the residual acid until it is neutral, and obtain a cellulose nanocrystal suspension CNC 30 ; Cellulose nanocrystal suspension CNC 30The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:200, and ultrasonic treatment was performed with an ultrasonic power of 1500 W and an ultrasonic time of 10 min. The cellulose nanocrystal suspension CNC with a mass concentration of 4.2% was obtained. 30 ;Cellulose nanocrystals CNC 30 The length is 223.6±18nm, the diameter is 7.5±0.4nm, and the aspect ratio is 30;
[0060] (4) The cellulose nanocrystal suspension CNC with a mass concentration of 4.2% was prepared by evaporation film forming method. 90 and CNC 30 The mixture was evenly mixed in a ratio of 8:2, and then the mixed solution was transferred to a polystyrene watch glass, evaporated to dryness at room temperature and evaporated for 5 days to self-assemble into a film, thereby obtaining a blue-green humidity-responsive cellulose nanocrystal structural color film.
[0061] Table 1 CNC size table under different acid decomposition time
[0062]
[0063] Comparative Example 1
[0064] (1) Soaking the crushed waste cotton powder in a NaOH solution with a mass concentration of 3% for 8 hours, and washing with distilled water to obtain the waste cotton powder after alkali pretreatment;
[0065] (2) Add the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 64%, heat and stir to hydrolyze for 30 minutes, and control the temperature at 45°C and the stirring speed at 300 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, add distilled water to dilute, and then centrifuge and wash at a speed of 5000 r / min for 10 minutes to remove the residual acid until it is neutral, and obtain a cellulose nanocrystal suspension CNC 30 ; Cellulose nanocrystal suspension CNC 30 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:200, and ultrasonic treatment was performed with an ultrasonic power of 1500 W and an ultrasonic time of 10 min. The cellulose nanocrystal suspension CNC with a mass concentration of 4.2% was obtained. 30 ;Cellulose nanocrystals CNC 30 The length is 223.6±18nm, the diameter is 7.5±0.4nm, and the aspect ratio is 30;
[0066] (3) Add the waste cotton powder after alkali pretreatment to concentrated sulfuric acid with a mass concentration of 64%, heat and stir to hydrolyze for 40 minutes, and control the temperature at 45°C and the stirring speed at 300 r / min during the heating and stirring hydrolysis process; after the hydrolysis is complete, add distilled water to dilute, and then centrifuge and wash at a speed of 5000 r / min for 10 minutes to remove the residual acid until it is neutral, and obtain a cellulose nanocrystal suspension CNC 40 ; Cellulose nanocrystal suspension CNC 40 The cellulose nanocrystal solution was prepared with deionized water at a mass ratio of 1:200, and ultrasonic treatment was performed with an ultrasonic power of 1500 W and an ultrasonic time of 10 min. The cellulose nanocrystal suspension CNC with a mass concentration of 4.2% was obtained. 40 ;Cellulose nanocrystals CNC 40 The length is 188.2±23nm, the diameter is 6.5±0.5nm, and the aspect ratio is 29;
[0067] (4) The cellulose nanocrystal suspension CNC with a mass concentration of 4.2% was prepared by evaporation film forming method. 40 and CNC 30 The mixture was mixed evenly in a ratio of 9:1, and then the mixed solution was transferred to a polystyrene surface dish, evaporated to dryness at room temperature and evaporated for 5 days to self-assemble into a film, obtaining an orange-red cellulose nanocrystal structural color film. The two cellulose nanocrystals have poor performance in regulating the color of the film, and the obtained film can only be orange-red, and the red film cannot be adjusted to a blue film.
[0068] Figure 1 The color change of the humidity-responsive cellulose nanocrystal structure color film under different relative humidity, UV-Vis spectrum and cyclic response diagram are shown in Example 5. Figure 1 It can be seen that when the relative humidity gradually changes from 11% to 97%, the color of the humidity-responsive cellulose nanocrystal structural color film changes from blue-green to yellow and then to red, and the UV-Vis diffraction peak moves from 494nm to 621nm and then to 723nm. And there is no obvious loss in humidity-responsive color change performance within 10 cycles. This work realizes the efficient recycling of waste cotton, which is conducive to the utilization of waste resources and the conservation of primary resources.
[0069] Figure 2 This is the SEM image of the cross-section of the regenerated nanocrystal humidity-responsive color-changing structural color film of Example 5. It can be observed that the pitch of the film is uniform and there is no crack caused by phase separation.
[0070] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a humidity-responsive cellulose nanocrystal structural color film, characterized in that: The steps include: (1) The alkali-pretreated waste cotton powder was hydrolyzed with sulfuric acid to prepare a cellulose nanocrystal suspension, and regenerated cellulose nanocrystal suspensions CNC with different aspect ratios were prepared by controlling the time of sulfuric acid hydrolysis. n ; (2) CNC suspensions of regenerated cellulose nanocrystals with different aspect ratios n The mixture is uniformly mixed in different proportions and evaporated to induce self-assembly to form a film, thereby obtaining a humidity-responsive cellulose nanocrystal structural color film.
2. The method for preparing a humidity-responsive cellulose nanocrystal structural color film according to claim 1, characterized in that: In step (1), the waste cotton powder is soaked in a NaOH solution with a mass concentration of 3 to 10% for 8 to 10 hours to obtain the waste cotton powder pretreated with alkali.
3. The method for preparing a humidity-responsive cellulose nanocrystal structural color film according to claim 1, characterized in that: In step (1), regenerated cellulose nanocrystal suspensions CNC with different aspect ratios n The mass concentration is 2.0~8.4%.
4. The method for preparing a humidity-responsive cellulose nanocrystal structural color film according to claim 1, characterized in that: In step (1), the mass concentration of sulfuric acid is 60-65%.
5. The method for preparing a humidity-responsive cellulose nanocrystal structural color film according to claim 1, characterized in that: In step (1), regenerated cellulose nanocrystal suspensions CNC with different aspect ratios n In the experiment, the aspect ratio of regenerated cellulose nanocrystals is 15-35.
6. The method for preparing a humidity-responsive cellulose nanocrystal structural color film according to claim 1, characterized in that: In step (1), the acid hydrolysis time is 30 to 90 minutes.
7. The method for preparing a humidity-responsive cellulose nanocrystal structural color film according to claim 1, characterized in that: In step (2), regenerated cellulose nanocrystal suspensions CNC with different aspect ratios n , n represents the acid hydrolysis time, the hydrolysis time is 30 to 90 minutes; when n is 60 minutes and 30 minutes, the obtained CNC 60 and CNC 30 The mixture was mixed evenly in a mass ratio of 1:9 and evaporated to induce self-assembly film; when n was 70min and 40min, the obtained CNC 70 and CNC 40 The mixture was mixed evenly in a mass ratio of 2:8 and evaporated to induce self-assembly film; when n was 80min and 50min, the obtained CNC 80 and CNC 50 The mixture was mixed evenly in a mass ratio of 4:6 and evaporated to induce self-assembly film; when n was 90min and 60min, the obtained CNC 90 and CNC 60 The mixture was mixed uniformly at a mass ratio of 9:1 and evaporated to induce self-assembly film; when n was 90min and 30min, the obtained CNC 90 and CNC 30 The mixture was mixed evenly at a mass ratio of 8:2 and evaporated to induce self-assembly film.
8. The method for preparing a humidity-responsive cellulose nanocrystal structural color film according to claim 1, characterized in that: In step (2), the time for evaporation-induced self-assembly is 4 to 6 days.
9. The humidity-responsive cellulose nanocrystal structural color film prepared by the method according to any one of claims 1 to 8.
10. Application of the humidity-responsive cellulose nanocrystal structural color film according to claim 9 in the fields of environmental monitoring, medical diagnostic tools, and food processing safety.
Citation Information
Patent Citations
Preparation method of ramie bone cellulose nanocrystalline self-assembled structural color thin film
CN106380613A
Structural color film with humidity response characteristic and preparation method of structural color film
CN113681997A
Preparation method of nano cellulose composite film capable of responding to humidity and obtained product
CN114316373A
Preparation method of humidity response chiral photonic crystal film based on cellulose nanocrystals
CN117757117A
Multi-response Cellulose Nanocrystals-composite Film and Preparation Method Thereof
US20220106409A1